Evaluation of muscle tissue growth in Young Mediterranean Buffaloes slaughtered at different weights - dos Santos, T. A.B. [UNESP]; Jorge, A. M. [UNESP]; Pardo, R. B. [UNESP] (Taylor & Francis, 2007)
This study evaluated muscle, adipose and bone tissue growth in young Mediterranean buffaloes slaughtered with different weights. Twenty eight non-castrated males, approximately 14 months old and 330 kilos, were distributed in four experimental and one control groups. Received the same diet during a non-fixed period and when reached the pre-established weights (450 kg, 480 kg, 510 kg, 540 kg) were fasted for 16 hours and slaughtered. NRC 1996, level 2, ruminal simulation program for non-castrated animals with a daily weight gain of 1.40 kg determined percentage composition of experimental diet (dry matter): coast cross hay (20.6%), corn silage (7.8%), cotton seed (8.2%), humid corn silage (46%) and commercial mineral concentrate (17.4%), representing 13% of crude protein and 2,68% of metabolizable energy (Mcal/kg). Feed was offered ad libitum twice daily. Slaughter of control group occurred after 30 days of an adaptation period. The other ones were weighted each 28 days until reached pre-established weight. Carcasses were chilled for 18 hours under -5°C. Ninth, 10° and 11° ribs of the half left carcass were submitted to HH section and according to the statistical regression analysis (SAS, 1996), allometric coefficient value was negative (b<1) demonstrating the early growth of muscle in relation to empty carcass weight.
Keywords: Buffalo; Muscle tissue